The k-pop idol in focus of Applied Linguistics: a discursive analysis of character construction in fanfiction - Andrade, Jandara Assis de Oliveira; Alves, Maria da Penha Casado; Silva, Juan dos Santos (Revista Letras Raras, 2024)
This paper analyzes the discursive construction of fanfiction character made by fan-author, considering that character is based on a real person, an idol from the South Korean pop music (K-pop) boyband BTS. This construction is shaped by how this fan-author perceives Asian men's masculinity. In this process, two aspects need to be observed, firstly the soft masculinity (Jung, 2010) performed by artist and the second is the characteristic vision of Asian man and the active/passive roles in same-sex relationships propagated by various Western social actors. To understand this process, it mobilizes the concepts of language, reflection and refraction (Bakhtin, 2015), ideological sign (Volochinóv, 2017), soft masculinity (Jung, 2010), performance (Buttler, 2017 ), masculinity (Kimmel, 2016), Queer theory (Louro, 2001, Miskolci, 2021), and passivity and activity (Foucault, 1984). In order to construct and analyze the data, it uses the Index Paradigm and Dialogical Comparison. The area in which it is located is Applied Linguistics as it understands that research is carried out on border between knowledge. Based on the analysis, it is possible to understand that Idol's actions, in the view of the South American fan, clash with a gender performance that corresponds to the heteronormative standard that he recognizes, meaning that, in construction of his text, the artist's characteristics are reflected and refracted in form of performance of a gay man or a Queer man who transgresses the standards of behavior expected for his gender role.